Dispersion and morphology analysis of PMMA/organoclay nanocomposites using the Ripley functions and determination of effective elastic properties. (15th May 2023) - Kouassi, A.Y.E.; Matadi Boumbimba, R.; Sangaré, M.K.; Koutsawa, Y.; Benelfellah, A.; Demais, V.
Highlights: PMMA matrix was reinforced by two type of organoclays (Cloisite 20A and Cloisite 30B) at weight fraction from 1 wt% to 5 wt%. Ripley functions K(r) and ImageJ software were used for dispersion and morphology analyses based on TEM images, respectively. Three aspect ratios were considered in the reconstruction of the microstructures. 3D RVEs homogenization based on random dispersion of platelet and prism inclusions types were performed by Digimat-FE and elastic properties were also determined. The effective elastic properties increase with the volume fraction. The better properties were obtained for the smaller aspect ratio. The inclusion type doesn't have an important impact on the properties. The comparison of the effective Young moduli (E) to experimental data gives satisfactory result for the aspect ratio 0.02. Abstract: This paper deals with the microstructure of PMMA/organoclay nanocomposites and their effective elastic properties by the means of micro-mechanical modeling and numerical homogenization. PMMA matrix was reinforced by two types of organoclay (Cloisite 20A and Cloisite 30B) at both weight fraction from 1 w t % to 5 w t % . The microstructure characterization was based on the TEM images from which, Ripley functions K ( r ) and ImageJ software were used for organoclays dispersion and morphology analyses, respectively. Microstructures parameters such as elastic properties, volume fraction, random dispersion, platelet and prism inclusion types and aspect ratios were considered to 3D RVEs generation using Digimat-FE software. From the 3D RVEs, the numerical models were obtained and the effective elastic properties were determined by using Digimat-FE Solver. Thus, the variation of the computed properties has been investigated and illustrated. The Young's moduli ( E ) of each aspect ratio were compared to experimental data. From the results, the nanocomposite rigidity depends not only on the organoclays volume fraction in PMMA matrix but also on the dispersion state and the considered aspect ratio. The inclusion type would therefore not have an important impact on the effective elastic properties. Considering the same volume fraction and dispersion state of the organoclays, the best elastic effective properties were obtained for the smallest aspect ratio.